1997
DOI: 10.1023/a:1025615409383
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Short-term selective breeding starting from an F2 intercross of two inbred strains is a largely unexploited but potentially useful tool for quantitative trait locus (QTL) mapping. The selection lines can also serve as a valuable confirmation test of recombinant inbred (RI) QTL results when the same two progenitor strains are used. Starting from an F2 from a C57BL/6J (B6) X DBA/2J (D2) cross (B6D2F2), this approach was used in a population of approximately 72 mice per generation bidirectionally selected for two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
30
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(34 citation statements)
references
References 26 publications
4
30
0
Order By: Relevance
“…The realized heritability observed here is similar to that seen in the other published study using selective breeding to alter voluntary alcohol intake in mice with concurrent access to 10% ethanol and water (Belknap et al 1997), although HAP lines drink considerably more than the high line in that short-term selection study. Interestingly, heritability in the present study was over three times that observed using unidirectional selection for high blood alcohol levels in mice following the 2-h, single bottle drinking in the dark (DID) procedure (Crabbe et al 2009).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The realized heritability observed here is similar to that seen in the other published study using selective breeding to alter voluntary alcohol intake in mice with concurrent access to 10% ethanol and water (Belknap et al 1997), although HAP lines drink considerably more than the high line in that short-term selection study. Interestingly, heritability in the present study was over three times that observed using unidirectional selection for high blood alcohol levels in mice following the 2-h, single bottle drinking in the dark (DID) procedure (Crabbe et al 2009).…”
Section: Discussionsupporting
confidence: 87%
“…One genetic approach that is appealing both in terms of simplicity and face validity is to use selective breeding for differences in free-choice alcohol drinking. Beginning in the 1960’s, at least 6 pairs of high and low alcohol drinking rat lines have been developed (Eriksson 1968; Lumeng et al 1977; Mardones and Segovia-Riquelme 1983; Li et al 1993; Colombo 1997; Le et al 2001), as well as at least 2 sets of mouse lines (Belknap et al 1997; Grahame et al 1999). Lines resulting from these selections reliably show profound differences in alcohol intake resulting from fixation of divergent alleles at loci related to alcohol drinking.…”
mentioning
confidence: 99%
“…Preliminary evidence from recombinant BXD inbred mouse strains exposed to ethanol SIP indicated that adjunctive drinking as a trait was approximately 27–31% heritable, depending on the drinking measure evaluated (Goldowitz et al, 2006). A comparable realized heritability of 32% was reported in a short-term selection study for preference of a 10% ethanol solution in mice (Belknap, Richards, O’Toole, Helms, & Phillips, 1997). …”
Section: Significant Biological and Environmental Factors That Cosupporting
confidence: 75%
“…The HS-CC was derived from eight mouse strains, including three wild-derived strains; the genetic diversity captured is ∼90% of that available in M. musculus (Roberts et al, 2007). The preference lines were bred using a short-term selective breeding protocol (Belknap et al, 1997; Metten et al, 2014) that minimizes the stochastic fixation of alleles unrelated to the phenotype of interest, here 2-bottle choice ethanol preference. From the perspective of ethanol preference and consumption, the HS-CC are of interest in that ∼25% of the animals show a preference for ethanol; this differs from a <5% preference found in our HS/NPT mice (unpublished observation) that were derived from eight laboratory mouse strains (Hitzemann et al, 2014).…”
Section: Discussionmentioning
confidence: 99%